Actor Network (Study on the Network Basis of Yasir Mahmud's Electability as a Member of the South Sulawesi Provincial DPRD for the 2024-2029 Period) - B, Mujiburrahman; Muhammad, ‎; Kambo, Gustiana A. (KnE Social Sciences, 2025)
This study aims to analyze the basis of actor networks (Actor-Network Theory/ANT) in shaping Yasir Mahmud’s electability as a member of the South Sulawesi Provincial DPRD for the 2024–2029 period. The ANT approach is used to explore the role of human and non-human actors—such as social relations, campaign technology, and local cultural structures—in mediating power dynamics and electoral strategies. This study relies on in-depth interview techniques and documentation as data collection methods, as well as qualitative analysis based on data reduction, presentation, and verification. The results of the study show that strong social networks, cultural closeness to the Bone community, and the use of economic narratives through experience as a fertilizer entrepreneur are the keys to Yasir Mahmud’s success. In addition, a patronage-based approach, local values such as siri’ na pacce, and community empowerment strategies play an important role in building voter loyalty. This study emphasizes that electability in the local context cannot be separated from the complex relations between social, cultural, economic, and technological structures. ANT is a relevant analytical framework for understanding how political agency is formed in a network of mutually constructing networks.